Pengaruh Metode Pembelajaran Konvensional dan Game terhadap Pembelajaran KWU dalam Meningkatkan Minat Belajar SMAN 4 Pasuruan - Sherly Zakia Ningtyas; Sugeng Pradikto (Jurnal Kajian dan Penelitian Umum, 2025)
This research aims to analyze the influence of conventional learning methods and game-based methods on students' interest in learning in Entrepreneurship subjects (KWU) at SMAN 4 Pasuruan. Interest in learning is a key indicator of successful learning, so an innovative and relevant approach is needed to improve it. In this research, a qualitative approach was used with in-depth interview methods as the main data collection technique. The research respondents involved students from SMAN 4 Pasuruan. Apart from that, this research also utilizes literature from trusted sources regarding the effectiveness of game-based and conventional learning methods. The research results show that conventional methods, which rely heavily on lectures and assignments, are less able to attract students' attention optimally. This is especially seen in material that requires creativity, emotional involvement, and active participation from students. On the other hand, educational game-based learning methods have significant advantages in creating a learning atmosphere that is more interactive, fun and relevant to students' needs. Educational games are proven to be able to connect theoretical concepts with practice through real-world simulations, which directly increase students' interest in learning. This research concludes that combining conventional methods with game-based learning can be an effective solution in increasing students' interest in learning.